1983
DOI: 10.1172/jci111116
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of rat liver hydroxymethylglutaryl coenzyme A reductase by a new class of noncompetitive inhibitors. Effects of dichloroacetate and related carboxylic acids on enzyme activity.

Abstract: A B S T R A C T Dichloroacetate (DCA) markedly reduces circulating cholesterol levels in animals and in patients with combined hyperlipoproteinemia or homozygous familial hypercholesterolemia (FH). To investigate the mechanism of its cholesterol-lowering action, we studied the effects of DCA and its hepatic metabolites, glyoxylate and oxalate, on the activity of 3-hydroxy-3-methylglutaryl coenzyme A reductase (HMG CoA reductase) obtained from livers of healthy, reverse light-cycled rats. Oral administration of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

1985
1985
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(12 citation statements)
references
References 44 publications
2
9
0
Order By: Relevance
“…Our studies show that the cholesterol-lowering drug, DCA, at a single dose lower than that reported to decrease cholesterol levels in patients with diabetes (34) or homozygous familial hypercholesterolemia (35), rapidly but transiently inhibited enzyme activity. These results are consistent with those obtained in rat liver (39) and cultured human lymphoid (IM-9) cells (32).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our studies show that the cholesterol-lowering drug, DCA, at a single dose lower than that reported to decrease cholesterol levels in patients with diabetes (34) or homozygous familial hypercholesterolemia (35), rapidly but transiently inhibited enzyme activity. These results are consistent with those obtained in rat liver (39) and cultured human lymphoid (IM-9) cells (32).…”
Section: Discussionsupporting
confidence: 92%
“…Dichloroacetate reduces cholesterol levels in man (34,35), inhibits hepatic cholesterol biosynthesis in rats (39) and is a noncompetitive inhibitor of HMG CoA reductase obtained from rat liver (39). Previous studies have also shown that dichloroacetate inhibits human leukocyte HMG CoA reductase activity in vitro (32).…”
Section: Methodsmentioning
confidence: 99%
“…As described in figure 2 and figure 3, the active component of DADA on keratinocytes is DCA, at least in vitro, which coincides with the cases previously reported on increasing vasodilation [26], lowering blood glucose in hyperglycemia [5] and suppressing lipid syn- Kitamura/Ota/Mimura thesis [27]. DCA is known to activate the pyruvate dehydrogenase complex by phosphorylating and inhibiting pyruvate dehydrogenase kinase [28], a regulatory protein of pyruvate dehydrogenase.…”
Section: Discussionsupporting
confidence: 87%
“…DCA's inhibitory effect is observed in both rodent liver [5] and human leukocytes [6]; it likely accounts for the drugassociated reduction in total and lowdensity lipo protein (LDL) cholesterol in patients with LDL receptornegative homozygous familial hyper cholesterolemia [7] and for its desig nation as the first orphan product for this rare disease. Second, DCA inhibits de novo hepatic triglyceride synthesis in nondiabetic rodents [5] and decreases circulating triglyc eride and very low density lipoprotein levels in patients with Type 2 diabetes mellitus [4]. It also decreases blood ketone bodies in rats with experimentally induced diabetic ketoacidosis [8,9].…”
Section: Clinical Use Of Dichloroacetatementioning
confidence: 99%